2013
DOI: 10.1155/2013/645817
|View full text |Cite
|
Sign up to set email alerts
|

Soy Saponins Meditate the Progression of Colon Cancer in Rats by Inhibiting the Activity ofβ-Glucuronidase and the Number of Aberrant Crypt Foci but Not Cyclooxygenase-2 Activity

Abstract: Objective. The effect of extracted crude soybean saponins on preneoplastic lesions, aberrant crypt foci (ACF), and the related mechanism were investigated. Research Methods and Procedures. Rats were assigned into five groups according to different doses of extracted crude soybean saponins and received 1,2-dimethylhydrazine (DMH) injection in week 5. In week 15, all rats were sacrificed. The number of ACFs, the cyclooxygenase-2 (COX-2) protein expression, the level of prostaglandins E2 (PGE2), and the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Meanwhile, all rats injected with AOM developed ACF containing different numbers of crypts ( Table 3 ). In agreement with previously published findings, ACF formation in the distal colon was significantly higher than the proximal colon [ 20 , 42 ]. Compared with the cancer control group, the administration of 5-FU or EEAML at 250 mg/kg or 500 mg/kg significantly suppressed the formation of ACF (79.5%, 61.2% and 72.5%, respectively).…”
Section: Resultssupporting
confidence: 93%
“…Meanwhile, all rats injected with AOM developed ACF containing different numbers of crypts ( Table 3 ). In agreement with previously published findings, ACF formation in the distal colon was significantly higher than the proximal colon [ 20 , 42 ]. Compared with the cancer control group, the administration of 5-FU or EEAML at 250 mg/kg or 500 mg/kg significantly suppressed the formation of ACF (79.5%, 61.2% and 72.5%, respectively).…”
Section: Resultssupporting
confidence: 93%
“…Modelos animales y celulares sugieren que las saponinas contenidas en las legumbres podrían estar mediando este efecto protector sobre el epitelio intestinal. En particular, una dieta suplementada con harina de garbanzo (10%) por 10 semanas fue efectiva para disminuir un 64% la formación de focos aberrantes de criptas colónicas en un modelo murino de tumores inducidos 65,66 . Experimentalmente, la incubación con apigenina (0-50 μM) por 24 horas en células HCT116 resultó en el arresto celular de esta línea celular, un efecto mediado por el aumento en la expresión de proteínas p53, p21CIP1 y WAF1, las cuales inhiben a la quinasa dependiente de ciclina 30,67 .…”
Section: Cáncer Colo-rectalunclassified
“…The result of this study appears to be in line with previous studies, which reported a higher number of ACF in distal parts of the colon compared to the proximal parts. 31 , 32 The consequent ACF detriment was significantly attenuated by administration of DECPR at 250 mg/kg and 500 mg/kg concentrations with an inhibitory percentage of 56.04% and 68.68%, respectively. A number of published findings on other Curcuma spp.…”
Section: Resultsmentioning
confidence: 96%